Mortality risk in irritable bowel syndrome: results from a nationwide, prospective cohort study - Staller, Kyle (Am J Gastroenterol, 2020)
OBJECTIVES: Mortality concern is a frequent driver of care-seeking in patients with irritable bowel syndrome (IBS). Data on mortality in IBS are scarce and population-based studies have been limited in size. We examined mortality in IBS. METHODS: Nationwide, matched population-based cohort study in Sweden. We identified 45,524 patients with a colorectal biopsy at any of Sweden’s 28 pathology departments and a diagnosis of IBS 2002-2016 according to the National Patient Register, a nationwide registry of inpatient and outpatient specialty care. We compared mortality risk between these individuals with IBS and age- and sex-matched reference individuals (n=217,316) from the general population as well as siblings (n=53,228). In separate analyses, we examined the role of mucosal appearance for mortality in IBS. Finally, we examined mortality in 41,427 IBS patients without a colorectal biopsy. Cox regression estimated hazard ratios (HRs) for death. RESULTS: During follow-up, there were 3,290 deaths in IBS (9.4/1000 person-years) compared to 13,255 deaths in reference individuals (7.9/1000 person-years); resulting in an HR of 1.10 (95% CI=1.05-1.14). After adjustment for confounders, IBS was not linked to mortality (HR=0.96; 95%CI=0.92-1.00). Risk estimates were neutral when IBS patients were compared to their siblings. Underlying mucosal appearance on biopsy had only a marginal impact on mortality, and IBS patients without colorectal biopsy were at no increased risk of death (HR=1.02; 95%CI=0.99-1.06). CONCLUSIONS: IBS does not seem to confer an increased risk of death.